Rapid resolution liquid chromatography method development and validation for simultaneous determination of homocysteine, vitamins B(6), B(9), and B(12) in human serum - Shaik, Munvar Miya (Medknow Publications & Media Pvt Ltd, 2013)
AIM: Hyperhomocysteinemia and vitamins B(6), B(9), and B(12) deficiencies usually result in various neurological, vascular, ocular, renal, and pulmonary abnormalities. However, to date, there are no simultaneous detection methods available for determining homocysteine, vitamins B(6), B(9), and B(12) levels in various biological fluids. In this study, we aim to develop a new validated simultaneous detection method for all four compounds to save both cost and time of analysis. MATERIALS AND METHODS: The mobile phase consisted of a mixture of methanol and 1-heptanesulfonic acid sodium salt (33:67) with 0.05% triethylamine. The pH of the entire mixture was adjusted to 2.3 and the flow rate was 0.5 mL/min. Separation was achieved using a C-18 column (5 μm; 150 mm × 4.6 mm) maintained at 28°C in a column oven and the detection was conducted at 210 nm. RESULTS: The method was linear between 50 and 1600 ng/mL for all of the drugs. The limits of detection for homocysteine, vitamins B(6), B(9), and B(12) were 5, 5, 10, and 10 ng/mL, respectively, while the limits of quantification were 10, 10, 25, and 25 ng/L, respectively. The developed method achieved good precision and accuracy and complies with the Food and Drug Administration (FDA) requirements. CONCLUSION: The developed and validated method is suitable to be used for the routine analysis of homocysteine, vitamins B(6), B(9), and B(12) simultaneously in human serum.